Diagnosis and treatment of pediatric chronic osteomyelitis in developing countries: prospective study of 96 patients treated in Kenya. - Mantero, E; Carbone, M; Calevo, M G; Boero, S (Musculoskelet Surg, 2011)
The authors carried out a prospective study on 96 patients they treated in Kenya for chronic osteomyelitis from 2000 to 2009. All the patients received orthopedic surgery and antibiotic therapy, when possible based on the antibiotic sensitivity test. Among the 90 patients with at least 12 months' follow-up, 11 had osteomyelitis relapse (12.2%) and recovery rate was therefore 87.8% with no resulting disability. Risk factors for osteomyelitis relapse were investigated and previous treatment with beta-lactamines, predisposing to onset of methycillin-resistant Staphylococcus aureus (MRSA) infections (P = 0.03, OR = 5.74), and onset of osteomyelitis in the metaepiphyseal region (P < 0.0001) resulted statistically significant. Aim of the study was to evaluate the validity of our treatment of chronic osteomyelitis in Kenya on the basis of outcome.
Keywords: Adolescent; Algorithms; Anti-Bacterial Agents; Child; Chronic Disease; Developing Countries; Female; Follow-Up Studies; Humans; Kenya; Male; Methicillin-Resistant Staphylococcus aureus; Microbial Sensitivity Tests; Osteomyelitis; Prospective Studies; Recurrence; Reproducibility of Results; Risk Factors; Staphylococcal Infections; Treatment Outcome